1998
DOI: 10.1063/1.477310
|View full text |Cite
|
Sign up to set email alerts
|

Theory of vibrational relaxation processes in resonant collisions of low-energy electrons with large molecules

Abstract: The effect of intramolecular vibrational relaxation in resonant collisions of low-energy electrons with large molecules is investigated. The vibrational relaxation results from the coupling of a few active modes, which are strongly coupled to the electronic degrees of freedom and therefore coherently excited during the formation of the collision complex, to a large number of inactive bath modes. The theory is formulated within the framework of the projection-operator formalism. Starting from a model Hamiltonia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(22 citation statements)
references
References 82 publications
0
22
0
Order By: Relevance
“…The SF À 6 anion becomes metastable, and this explains the nondissociative feature of low-energy attachment to SF 6 (see also Thoss and Domcke, 1998). Since the capture in this case is nonresonant, the VW model becomes appropriate.…”
Section: B3 Electron Attachment To Sf 6 and CCLmentioning
confidence: 99%
“…The SF À 6 anion becomes metastable, and this explains the nondissociative feature of low-energy attachment to SF 6 (see also Thoss and Domcke, 1998). Since the capture in this case is nonresonant, the VW model becomes appropriate.…”
Section: B3 Electron Attachment To Sf 6 and CCLmentioning
confidence: 99%
“…Since the dissociative attachment channel is closed at low energies, attachment occurs through vibrational energy redistribution whereby the vibrational energy initially concentrated in the active modes of one molecular unit is redistributed among other intramolecular and intermolecular modes (so-called bath modes) and is thus not available for the autodetachment of the electron on the time scale of the experiment; this process is well known in molecular spectroscopy [19]. Thoss and Domcke [20] showed that this process in electron collisions can be taken into account by adding an energy independent width and shift to the active-mode Hamiltonian. In ERT the shortrange part of the electron-molecule interaction is incorporated by a boundary condition of the form…”
mentioning
confidence: 99%
“…It is coupled to electronic states with ener- the harmonic mode and the electronic state is denoted by λ. In addition, we consider a direct coupling of the local vibrational degree of freedom to a bath of oscillators [33,[86][87][88].…”
Section: Theory a Model Hamiltonianmentioning
confidence: 99%